Vocabulary Learning Strategies in DOTA 2: A Case Study of Players' Viewpoints - Herwanto, Wanda Hijriani; Setiawan, Slamet; Munir, Ahmad (Fakultas Bahasa dan Seni UNP, 2025)
The popularity of video games among language learners makes games a potential medium for learning languages. Previous research shows that playing video games, one of which is DOTA 2, can have a positive effect on students' vocabulary acquisition, but it still does not explain what specific vocabulary learning strategies are used. This study explores DOTA 2 players' experiences in acquiring new knowledge and identifies effective strategies for acquiring knowledge in the context of the game. The research method used is a case study research design, as well as semi-structured interviews and observation. The results showed that DOTA 2 players learned new vocabulary through exposure while playing the game, and social interaction was the most emphasized comprehension learning strategy used by the participants. This study provides insight into the effectiveness of DOTA 2 as a language learning tool, especially regarding knowledge acquisition.